TINJAUAN TEOLOGIS PSIKOLOGIS KEPRIBADIAN GANDA DALAM KEHIDUPAN HAMBA TUHAN DI MASA INI - Yusak Noven Susanto (Alucio Dei, 2020)
In the postmodern world humans have different characteristics from one another. Tempramen is the nature of birth, why is that because since an individual is born into the world he inherits inherited traits rather than his parents. Usually temparen can change due to one's environment and emotions and this can shape the individual's temperament. Every trait or temperament that exists in an individual there are also positive things and negative things in them. Positive qualities will have a good effect on the personality of the individual. But on the contrary negative traits will adversely affect human personality. Multiple personality or dissociative identity disorder is a serious disorder because in an individual there are two or more personalities and from each personality it controls his behavior. The cause of multiple personalities is an innate ability to easily separate personality, repeated sexual harassment, lack of people who protect or entertain from bad experiences. Influence from other family members who have psychological disorders. This multiple personality disorder can be cured by a sufferer through his acknowledgment and awareness that he has multiple personalities and is balanced by a strong desire to heal and pray to God so that the Holy Spirit can be a comforter and helper in the process of healing this dual personality.